Cabassous tatouay (Cingulata: Dasypodidae). (11th September 2014) - Hayssen, Virginia
Abstract: Cabassous tatouay (greater naked-tailed armadillo) is the largest naked-tailed armadillo. This fossorial denizen of forest and savanna habitats burrows for ants and termites in east-central South America. C. tatouay is listed as "Least Concern" by the International Union for Conservation of Nature and Natural Resources.